Relationships between executive function, working memory, and decision‐making on the Iowa Gambling Task: Evidence from ventromedial patients, dorsolateral patients, and normal subjects - Ouerchefani, Riadh; Ouerchefani, Naoufel; Allain, Philippe; Ben Rejeb, Mohamed Riadh; Le Gall, Didier (Journal of neuropsychology, 2019)
The results of previous studies are inconsistent in regard to the relationship between the Iowa Gambling Task (IGT), working‐memory (WM), and executive tasks, and whether these cognitive processes could be considered as mechanisms underlying a decision‐making deficit. Moreover, the relationship between the IGT and executive measures is examined based on a limited number of executive tasks, within different populations showing diffuse damage. In addition, there are fewer studies carried out within control participants, with those studies also being inconclusive. It is also suggested that the association of the IGT performance with executive tasks depends on whether the IGT was running under ambiguity or under risk. In this work, all of these issues are studied. Results showed that both patients with ventromedial (VMPFC, N = 10) and dorsolateral (DLPFC, N = 10) prefrontal cortex lesions are significantly impaired on almost all executive tasks, WM tasks, and the IGT. Furthermore, when the IGT is run under risk, there are significant correlations between executive measures and the IGT for the DLPFC patients and the control participants (N = 34) but not the VMPFC patients. No correlation was found between WM tasks and the IGT for both frontal subgroups and control participants. These findings suggested that the mechanisms underlying the IGT deficit differ according to the lesion locations.